Confirmatory factor analysis sosiomathematics norm among junior high school student - Sri Adi Widodo; T. Turmudi; Jarnawi Afgani Dahlan; Esti Harini; Fitria Sulistyowati (International Journal of Evaluation and Research in Education (IJERE), 2020)
The purpose of this study was to confirm the factors that influence the sociomathematics norm. The method used in this research is the ex post facto. The subjects in this study were seventh-grade junior high school students in the city of Yogyakarta, Indonesia (264 students) taken by cluster random sampling. The instrument used was a sociomathematics norm observation sheet consisting of four factors are (1) the experience of mathematics, (2) the explanation of the mathematics, (3) mathematical differences, (4) mathematical communication. Data analysis using structural equation models with the Confirmatory Factors Analysis. The results showed that the modified path analysis obtained goodness of fit mostly in the fit category, so overall the sample covariance matrix is the same as the estimated covariance matrix.